Efek Penambahan Cuka Aren (Arenga pinnata) pada Ikan Tongkol (Euthynnus affinis) terhadap Jumlah Mikroba dan Waktu Awal Pembusukan - Rastina Rastina; Elvi Gustina Siregar; Filna Muharani; Fakhrurrazi Fakhrurrazi; Ismail Ismail; Darniati Darniati; Herrialfian Herrialfian; Siti Rani Ayuti; Ali Makmur (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Tuna meat is a food ingredient with a high nutrient content, especially protein. This causes tuna meat cannot be stored for a long time, because it is easily damaged. To overcome this, you can add natural preservatives using palm vinegar (Arenga pinnata). This study aims to analyze the number of microbes and detect the initial time of decay in tuna (Euthynnus affinis) added with palm vinegar (Arenga pinnata). The research design used a completely randomized design (CRD), which consisted of 3 treatments and 3 repetitions. These 3 treatments were carried out by soaking 225 grams of tuna with palm vinegar at concentrations of 0%, 2.5% and 5% with 0 time. , 3, 6, and 9 hours. Determination of the number of microbes in this study was carried out using the Total Plate Count (TPC) method. The results showed that there was microbial contamination in tuna, and the higher the concentration of palm vinegar, the smaller the chance of microbial contamination. In the spoilage test with 6 hours of immersion of tuna meat with a concentration of 0% and 2.5%, the initial decay occurred, and at a concentration of 5%, the initial spoilage did not occur. It can be concluded that the use of palm vinegar with a concentration of 2.5% can reduce the amount of microbial contamination. Palm vinegar with a concentration of 5% can inhibit spoilage, and slow down the initial time of decay in tuna.